Nanotechnology Safety as a New Challenge for Occupational Health and Safety - Danihelka, Pavel; Van Tongeren, Martie; Sikorova, Lucie; Brzicova, Tana (Communications - Scientific letters of the University of Zilina, 2015)
Nanotechnology as a key enabling technology offers great potential for economy and society, but may also bring new threats to workers´ health due to new aspects of hazard, ways of transport, nanoparticles transformation and accumulation. Even if principal paradigms of classical toxicology are probably applicable to nanostructured materials, important gaps still exist. One of the most important topics to be developed is the occupational exposure assessment with special attention paid to the exposure measurement and exposure scenarios building. This article brings insight into the state-of-the-art of the nanotechnology safety and analyses key needs in this new safety domain.